Hematocrit effects on Blood flow through an overlapping stenosed artery with permeable wall - Abiodun Babatunde; Moses Dada (Journal of Heat and Mass Transfer Research, 2021)
ABSTRACTThis present study discusses the contributions of the presence of hematocrit level on wall shear stress and flow resistance in a tapered and overlapping stenosed artery with permeable wall. It enables the prediction of the main property of the physiological flows which plays an important role in biomedical investigations. The equation governing the flow in a tapered overlapping stenosed artery was simplified and solved analytically for resistance to flow and wall shear stress. The results highlight that the resistance to flow increases with an increase in either stenosis height or artery shapes while It decreases slightly with a rise in hematocrit level within normal range. Darcy number rises as the resistance to flow decreases for non-tapering, diverging tapering and converging tapering artery shapes. There is a significant hike in wall shear stress as slip parameter or Darcy number increases for diverging tapering, non-tapering and converging tapering. Also, the wall shear stress is increasing with an increase in stenosis height and a decrease in artery shapes.